Ovine male genital duct epithelial cells differentiate in vitro and express functional CFTR and ENaC. - Bertog, M; Smith, D; Bielfeld-Ackermann, A; Bassett, J; Ferguson, D; Korbmacher, C; Harris, A (2000)
To investigate the biology of the male genital duct epithelium, we have established cell cultures from the ovine vas deferens and epididymis epithelium. These cells develop tight junctions, high transepithelial electrical resistance, and a lumen-negative transepithelial potential difference as a sign of active transepithelial ion transport. In epididymis cultures the equivalent short-circuit current (I(sc)) averaged 20.8+/-0.7 microA/cm(2) (n = 150) and was partially inhibited by apical application of amiloride with an inhibitor concentration of 0.64 microM. In vas deferens cultures, I(sc) averaged 14.4+/-1.1 microA/cm(2) (n = 18) and was also inhibited by apical application of amiloride with a half-maximal inhibitor concentration (K(i)) of 0.68 microM. The remaining amiloride-insensitive I(sc) component in epididymis and vas deferens cells was partially inhibited by apical application of the Cl(-) channel blocker diphenylamine-2-carboxylic acid (1 mM). It was largely dependent on extracellular Cl(-) and, to a lesser extent, on extracellular HCO(-)(3). It was further stimulated by basolateral application of forskolin (10(-5) M), which increased I(sc) by 3.1+/-0.3 microA/cm(2) (n = 65) in epididymis and 0.9+/-0.1 microA/cm(2) (n = 11) in vas deferens. These findings suggest that cultured ovine vas deferens and epididymis cells absorb Na(+) via amiloride-sensitive epithelial Na(+) channels (ENaC) and secrete Cl(-) and HCO(-)(3) via apical cystic fibrosis transmembrane conductance regulator (CFTR) Cl(-) channels. This interpretation is supported by RT-PCR data showing that vas deferens and epididymis cells express CFTR and ENaC mRNA.